Pengaruh Problem Based Learning Terhadap Kemampuan Berpikir Kritis Matematis Siswa Sekolah Dasar - Setiawan , Renaldo Adam; Dewi , Happy Indira (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2024)
Problem Based Learning is a learning model that presents problems at the beginning of learning in students’ real lives. In this study, the aim was to determine the effect of using the Problem Based Learning PBL Learning Model on the ability to think mathematically critically in two classes with a total of 64 studentsin grade V at SDN Tomang 01 in the 2023/2024 academic year.Themodelin thisstudyis a quantitative typewith a true-experimental design.The instrument used in thisstudywas a posttest-onlycontrol design.The total populationconsistsof classV, which consists of class VA with 32 students, VB with 32 students, and VC with 32 students. The population used is two classes taken as research samples using a cluster random sampling technique, namely class VA and class VB. The data collection technique in this study used an instrumentinthe formof amathematical criticalthinkingabilitytest.After analyzingthedatausing the t-test obtained t count= 4.39 and t table = 1.99 at a significantlevel of 0.05.Thisshowsthat Ha is accepted, meaning that there is an influence of the Problem Based Learning Model on the mathematical criticalthinkingskills offifth-grade students at SDNTomang 01